Drying kinetics and physiological quality of 'Cabacinha' pepper seeds during storage - Silva, Hellismar W. da; Vale, Luis S. R.; Silva, Camila F.; Souza, Rannie do C.; Soares, Renato S. [UNESP] (Univ Federal Campina Grande, 2018)
Drying air temperature has direct influence on seed quality, especially for vegetable species harvested with high moisture content. This study aimed to determine and model the drying curves of 'Cabacinha' pepper seeds (Capsicum chinense L.) at different temperatures, and to evaluate their physiological quality after drying and during storage. The experimental design was completely randomized in a 3 x 3 factorial scheme, with three drying temperatures ( 35, 38 and 42 degrees C) and three storage periods (0, 4 and 8 months), with four replicates. Seed quality was evaluated by germination test, first germination count, accelerated aging, electrical conductivity, seedling emergence, and speed of emergence. The Two Terms is the model that best represents the drying curves of 'Cabacinha' pepper seeds at temperatures of 35, 38 and 42 degrees C. Higher germination and vigor values are obtained in seeds dried at 35 and 38 degrees C. Drying at 42 degrees C and storage reduce the physiological quality of the seeds.
Keywords: Capsicum chinense L.; drying temperature; germination; vigor